Effect of Pastor’s Church Ministry on their Family Stability in Nairobi County, Kenya - Maina, Jaccobed W.; Kaaria, Zipporah; Kivanguli, Gregory (European Scientific Journal, ESJ, 2018)
The family is an important place for individual mental growth. Pastors’ families, however, experience ministry related challenges with potential ramifications on their family stability. The specific objectives were; To find out the extent to which pastors work as a preacher affects family stability in selected churches in Eastlands – Nairobi County, to establish the extent to which pastoral care work affects family stability, and to determine the extent to which church administration work affects family stability. The research was guided by the Structural Family Theory developed by Salvador Minuchin and Family Systems theory propounded by Murray Bowen. Descriptive survey design was used. The sample of 166 respondents comprised of pastors, pastors’ spouses and adult children. Data were collected using a structured questionnaire and analyzed using descriptive statistical techniques. Hypotheses were tested using Spearman’s rank correlation technique at p<.05. The results showed that the relationship between preaching and family stability was not statistically significant. However, it was found that church administration and pastoral care had a significant negative correlation with family stability. It was recommended that the church needs to find ways of mitigating negative effects of church ministry by professionalizing its human resource systems and engaging professional counsellors for pastors and their families.